Associations of father’s breastfeeding attitude and support with the duration of exclusive breastfeeding among first-time mothers - Phua, Hui Wen; Abdul Razak, Nur Aina Afrina; Mohd Shukri, Nurul Husna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Initiating and sustaining breastfeeding are influence by many factors including involvement, attitude and support from the partner. Research on breastfeeding mostly investigate maternal factors, although the father’s behaviour and role may influence the success of breastfeeding. Hence, this study aimed to determine the associations of father’s attitude and support with the duration of exclusive breastfeeding new parents. Methods: The study involved 104 new parents in Kuala Lumpur, Malaysia, recruited at three randomly selected antenatal clinics using purposive sampling. Fathers’ breastfeeding attitude was measured using Iowa-Infant-Feeding-Attitude-Scale, whereas paternal support using Subjective Norms and Paternal-Breastfeeding-Influence-Scale questionnaires. Mothers were asked about breastfeeding practice. Results: Exclusive breastfeeding duration rates at six months was 27.9%. The average score for paternal attitude on breastfeeding was 61.0 ±6.3, indicating father’s positive attitude towards breastfeeding. The mean score of paternal breastfeeding supports for subjective norms surrounding breastfeeding and overall support score were 4.3+0.6 and 4.06+0.6, respectively, demonstrating frequent paternal engaging and support in breastfeeding. Duration of exclusive breastfeeding were positively associated with the paternal attitude (β=0.235, p=0.027) and overall mean score for breastfeeding support (β=2.166, p=0.028), but negatively associated with support strategies score (β= -2.203, p=0.026). Conclusion: Overall, paternal support and positive attitude were associated with breastfeeding duration. It is important to increase public awareness on the important roles of fathers during the breastfeeding process such as emphasizing the husband’s role in supporting their wives to breastfeed, as well as the importance of paternal role in caring the baby, especially among new couples.